The impact of the habituation agenda in improving training services at the ambon religious education and training center - Abdul Kahar (12 Waiheru, 2024)
This research discusses the impact of the habituation agenda on improving training services at B.D.K. Ambon. A qualitative descriptive study was conducted in 2024 for 8 CPNS BDK Ambon as L.A.T.S.A.R.’s participants to explain the implementation of the habituation agenda to actualize the fundamental values of civil servants, namely A.N.E.K.A. The research examines how the habituation agenda was implemented and whether it impacted improving training services. Both primary and secondary data sources are the foundation of the research method, which includes data collection techniques such as interviews and documentation, as well as analysis techniques starting from data collection, reduction, presentation, and conclusion. The result indicates that the habituation agenda of 8 LATSAR CPNS BDK Ambon in 2021 acted as a process of instilling the fundamental values of civil servants, A.N.E.K.A., for 30 days at B.D.K. Ambon according to the actualization plan, which included three activities: scope in S.K.P., leader’s assignments and self-initiatives innovations to support training services. In general, the habituation agenda impacted enhancing the skills of civil servants in mastering technology due to the socialization activities and technology mastery training, namely the similar application, online training, and assessments, which contributes to a new working Culture based on information technology that improves training services. In particular, the impact of this agenda was able to enhance aspects of behavior, skills, and system transformation, as the training committee is greatly assisted by the availability of several guidebooks, manuals, and tutorial videos regarding the Simdiklat application, Online training, and the trainers’ assessment application. The employees of B.D.K. Ambon are also helped to use the E-kinerja application easily.